PENGARUH PENDEKATAN PROGRESIF TERHADAP PENINGKATAN KEMAMPUAN MAHASISWA DALAM PEMBUKTIAN DAN PENULISAN JURNAL MATEMATIKA - Kodirun, Kodirun (2014)
The aim of this research is to find out whether progressive learning approach can enhance students ability in proving and writing journal of mathematics. To answer the research problem mentioned, quasi experiment is applied. The number of students participating in the study as population was 87 from two parallel classes. One of two classes was chosen randomly to be given progressive approach. Progressive approach was applied to the experimental group with 41 students and conventional approach was applied to the control group with 46 students. The students were also categorized into three groups of grade point averages (GPAs): higher, mid, and lower level. This research was conducted in Mathematics Department of Universitas Halu Oleo, Kendari, Sulawesi Tenggara, Indonesia. The students were expected to have two competencies, journal writing and proving mathematics. Journal writing in mathematics and mathematical proof compentencies on Abstract Algebra 1 was measured by pre-test and post-test on both areas. Scores of these tests were analyzed with Anacova test, two-way Anova, t-test, and Mann-Whitney U test. The results of the research were (1) students' comptencies on journal writing in mathematics and mathematical proof belongs to the middle level; (2) students' competence and students' enhancement on writing mathematics under progressive learning approach group was better than that of conventional one; (3) students' competence and students' enhancement on proving mathematics under progressive approach was better than that of conventional one, but students' enhancement on proving mathematics at lower level of GPA was not significantly different. Tujuan penelitian ini adalah untuk menjawab pertanyaan apakah pembelajaran dengan pendekatan progresif dapat meningkatkan kemampuan mahasiswa dalam pembuktian matematis dan penulisan jurnal matematika. Dalam penelitian ini, peneliti menggunakan eksperimen semu. Banyaknya anggota populasi adalah 87 mahasiswa yang terdiri dari dua kelas paralel. Satu kelas yang terdiri dari 41 mahasiswa dipilih secara acak untuk mendapatkan pendekatan progresif. Kelas lainnya yang terdiri dari 46 mahasiswa mendapatkan pendekatan konvensional. Pengetahuan awal matematis mahasiswa dikategorikan menjadi kategori tinggi, sedang, dan rendah. Penelitian dilakukan di Jurusan Matematika Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Halu Oleo (UHO), Kendari, Sulawesi Tenggara, Indonesia. Kemampuan penulisan jurnal matematika dan kemampuan pembuktian matematis mahasiswa pada matakuliah Struktur Aljabar 1 diukur dengan tes awal dan tes akhir. Hasil tes awal dan tes akhir dianalisis dengan Anacova, Anova dua jalur, uji-t, dan uji Mann-Whitney U. Hasil penelitian ini adalah (1) kemampuan penulisan jurnal matematika dan kemampuan pembuktian matematis mahasiswa berkategori sedang; (2) kemampuan mahasiswa dan peningkatannya pada penulisan jurnal matematika untuk kelompok progresif lebih baik daripada kelompok konvensional; (3) kemampuan mahasiswa dan peningkatannya pada pembuktian matematis untuk kelompok progresif lebih baik daripada kelompok konvensional, tetapi peningkatan kemampuan mahasiswa pada pembuktian matematis untuk kelompok yang memiliki indeks prestasi akademik rendah tidak berbeda secara signifikan.